2004
DOI: 10.1227/01.neu.0000103447.30087.d3
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Angioplasty and Stenting versus Carotid Endarterectomy for Treatment of Asymptomatic Carotid Stenosis: A Randomized Trial in a Community Hospital

Abstract: CAS and CEA may be equally effective and safe in treating individuals with asymptomatic carotid stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
159
0
7

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(167 citation statements)
references
References 54 publications
1
159
0
7
Order By: Relevance
“…Patients with a carotid stenosis Ͼ80% and no symptoms or signs of cerebral ischemia were randomized between stenting and surgery (nϭ84 patients). 12 No events occurred in these patients.…”
Section: Kentuckymentioning
confidence: 81%
See 2 more Smart Citations
“…Patients with a carotid stenosis Ͼ80% and no symptoms or signs of cerebral ischemia were randomized between stenting and surgery (nϭ84 patients). 12 No events occurred in these patients.…”
Section: Kentuckymentioning
confidence: 81%
“…Five of these were completed randomized controlled trials comparing endovascular treatment of carotid stenosis with surgery (nϭ879 patients) 3,[11][12][13][14] ; the 5 other trials were stopped early (nϭ2299 patients). [15][16][17][18][19] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, so far there has been no evidence of CAS superiority over CEA. [6][7][8][9][10][11][12][13] In Brazil, practice of carotid surgery has more than 40 years, and a survey has been published about indications and about who would indicate that procedure: neurologists, cardiologists or vascular surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…30 A follow-up randomized trial of over 80 asymptomatic patients demonstrated similarly equivalent very low rates of complications in either arm. 31 The largest study so far (CAVATAS) 32 consisted mainly of carotid balloon angioplasty (74%) with a small number of implanted stents and randomized over 500 patients to CEA or endovascular therapy. It showed a periprocedural rate of stroke and death of approximately 10%, which was similar for both arms, but much higher than NASCET's rate.…”
Section: Early Randomized Studiesmentioning
confidence: 99%